Persepsi Mahasiswa Fakultas Hukum Universitas Nusa Cendana Terhadap Penghinaan Citra Tubuh (Body Shaming) di Lingkungan Kampus dan Media Sosial - Renatalia Urbalina Pa Tari; Daud Dima Talo; Bhisa Vitus Wilhelmus (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The purpose of this study is to analyze the perceptions of students of the Faculty of Law, Nusa Cendana University about body shaming in the campus environment and social media and how the regulation of criminal acts of body shaming in review of the Criminal Code and Laws outside the Criminal Code. This research method is an empirical juridical approach, namely research whose data is obtained through efforts to investigate existing realities in social life. The results of this study are that the perceptions of students are very diverse, most students know about body shaming, many students have been victims of body shaming, and some are often the perpetrators of body shaming. The acts of body shaming that are experienced form the thoughts of some students to fight back but more choose to remain silent. This thought causes a response where some students choose to shut down and close themselves, some become insecure and others choose to withdraw from their social environment. According to most students, body shaming is a dangerous thing. The regulation of the criminal offense of body shaming in terms of the Criminal Code, the relevant article is Article 315 of the Criminal Code and if it is reviewed from laws outside the Criminal Code, the relevant articles are Article 27 Paragraph (3) of the ITE Law, Article 5 of the TPKS Law and Permendikbud Ristek No.30 of 2021.